Road investment design in areas protected by the monuments conservator = Projektowanie inwestycji drogowych na obszarach objętych ochroną konserwatora zabytków - Juszczyk, Artur (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Design works on road construction plans for areas protected by conservation require a proper preparation, especially in terms of formality, which has been described in this paper. One has shown the various methods of conduct in the course of obtaining administrative decisions and related difficulties, which are dependent on the form of monument protection and the scope of the proposed building works. One has also raised a question regarding the law on the subject. One has suggested the consolidation of existing regulations and introduced the likely new direction that is currently in preparation.
Keywords: drogowe roboty budowlane; projektowanie dróg; obiekty zabytkowe; ochrona konserwatorska; pozwolenie na budowę; roadworks; design of roads; historic building; conservation protection; building permit